1991
DOI: 10.1111/j.1600-0447.1991.tb03133.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum melatonin levels in schizophrenic and schizoaffective hospitalized patients

Abstract: Conflicting results on changes of the diurnal melatonin rhythms of patients with affective disorders have been reported in the literature. The heterogeneous data may derive from the great discrepancy in the diagnostic criteria of different authors. A study of 12 schizoaffective and chronic schizophrenic psychotic patients found a constant pattern of an obliterated nocturnal melatonin rise only in the latter group. The presence or absence of the nocturnal melatonin rise was determined in drug-free hospitalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Consistent with our results, Ro binson et al [12] reported that depressed 1.00-hour plas ma levels of melatonin did not significantly change after 2 months of neuroleptic therapy in 4 schizophrenic pa tients. Smith et al [24], instead, found higher plasma lev els of melatonin in 8 psychiatric patients treated with chlorpromazine as compared to healthy controls, but in this study no information is given on the length of drug treatment or on the diagnostic category of patients, and no measurement of pretreatment plasma values of mela tonin was performed.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with our results, Ro binson et al [12] reported that depressed 1.00-hour plas ma levels of melatonin did not significantly change after 2 months of neuroleptic therapy in 4 schizophrenic pa tients. Smith et al [24], instead, found higher plasma lev els of melatonin in 8 psychiatric patients treated with chlorpromazine as compared to healthy controls, but in this study no information is given on the length of drug treatment or on the diagnostic category of patients, and no measurement of pretreatment plasma values of mela tonin was performed.…”
Section: Discussionsupporting
confidence: 82%
“…The influence of antipsychotic drugs on melatonin secretion has rarely been evaluated directly. The majority of available studies have compared either untreated with treated patients or have followed up patients after the initiation of antipsychotic treatment and have demonstrated unchanged melatonin levels (Beckmann et al 1984;Robinson et al 1991;Rao et al 1994;Monteleone et al 1997). However, previous studies on the effect of chlorpromazine given to psychiatric patients have demonstrated increased melatonin levels (Smith et al 1977(Smith et al , 1979.…”
Section: Introductionmentioning
confidence: 97%
“…Low levels of melatonin have also been reported in premenstrual dysphoric disorder [10] and panic disorder [11]. Conflicting results of melatonin levels were reported in eating disorders [12][13][14] as well as in schizophrenia [15,16].…”
Section: Melatonin and Psychiatric Disordersmentioning
confidence: 86%